PENGEMBANGAN METODE PRODUKSI DAN PEMASARAN STIK JAGUNG IKAN SEBAGAI PRODUK UNGGULAN EKSPOR GORONTALO - Herwin Mopangga; Idris Niode (Pendidikan Ekonomi FKIP Universitas Sriwijaya, in partnership with Asosiasi Profesi Pendidikan Ekonomi Indonesia (ASPROPENDO), 2017)
Maize and fish are excellent commodities of Gorontalo with abundant production and potential but relatively little contribution to the expansion of employment opportunities and community income. Lack of technological intervention makes them more often sold raw commodity without processing.Stick fish corn is a local product that tends to increase demand and market share. The number of IKM producers of corn sticks in the city of Gorontalo is relatively small compared to the production, potential and demand of products in local and national markets. Thanks to the efforts and innovations of SMEs partners, the constraints on quality, permissions, halal, packaging, production space, labor, financial administration administration until promotion and sales began to be overcome so that production and marketing continues to increase and expand to serve the demand from a number of major cities in Indonesia . Strategic partnerships between government, banking, non-governmental organizations,SME groups and more intensive and integrated universities are expected to improve quality and competitiveness so as to accelerate products through export markets. IKM stick management methods of fish maize generally relate to aspects of product quality, labor, capital, technology and marketing